Role of microRNAs in type 2 diseases and allergen-specific immunotherapy - Jakwerth, Constanze A.; Kitzberger, Hannah; Pogorelov, Dimitrii; Müller, Annika; Blank, Simon; Schmidt-Weber, Carsten B.; Zissler, Ulrich M. (Frontiers in Allergy, 2022)
MicroRNAs (miRs) have gained scientific attention due to their importance in the pathophysiology of allergic diseases as well as their potential as biomarkers in allergen-specific treatment options. Their function as post-transcriptional regulators, controlling various cellular processes, is of high importance since any single miR can target multiple mRNAs, often within the same signalling pathway. MiRs can alter dysregulated expression of certain cellular responses and contribute to or cause, but in some cases prevent or repress, the development of various diseases. In this review article, we describe current research on the role of specific miRs in regulating immune responses in epithelial cells and specialized immune cells in response to various stimuli, in allergic diseases, and regulation in the therapeutic approach of allergen-specific immunotherapy (AIT). Despite the fact that AIT has been used successfully as a causative treatment option since more than a century, very little is known about the mechanisms of regulation and its connections with microRNAs. In order to fill this gap, this review aims to provide an overview of the current knowledge.